Developing Student Creativity Through Project-Based Learning in Leather Media Product Design - Ezriani (Kirana Publisher (KNPub), 2026)
Craft media learning plays a strategic role in equipping students with the ability to process materials, techniques, and design concepts in an integrated manner. Leather media was chosen as the focus of the learning project because it has unique material characteristics and high artistic potential. Leather can be processed through various techniques, such as carving, pressing, sewing, and combinations with other materials, thus providing broad opportunities for students to explore the shape, texture, and function of the product. This study aims to develop student creativity through the application of project-based learning (PBL) in leather media product design in craft media learning. The study used a quantitative approach with a pre-experimental design in the form of a one-group protest–post-test design. The research subjects consisted of 20 students of the Craft Education Study Program at the Institut Seni Indonesia Padangpanjang, Indonesia. The results showed a significant increase in student creativity after the application of project-based learning. The average creativity score increased from 67.85 in the pretest to 82.60 in the posttest, with the t-test results showing a p value <0.05. The N-Gain value of 0.46 is in the moderate category, indicating that project-based learning is quite effective in developing student creativity. Therefore, it can be concluded that Project-Based Learning can be an effective alternative learning model in craft media learning to encourage student creativity and innovation.